Locksport a hacker's guide to lockpicking, impressioning, and safe cracking - Weyers, Jos; Burrough, Matt; Belgers, Walter; BandEAtoZ; Tolley, Nigel K. (No Starch Press, 2024)
"The ultimate guide to lockpicking and the competitive sport of bypassing locking systems. Covers locksport history and events, pin-tumbler lockpicking, impressioning, safe manipulation, and level lockpicking. Written by five champion locksporters. Includes step-by-step instructions and full-color illustrations"--
Includes index. - Description based on print version record and CIP data provided by publisher; resource not viewed
Keywords: Lock picking -- Handbooks, manuals, etc; Locksmithing -- Handbooks, manuals, etc; Safecracking -- Handbooks, manuals, etc; Crochetage; Guides, manuels, etc; Serrurerie; Guides, manuels, etc